2023
DOI: 10.1002/adma.202310872
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Separated Lipid‐Based Nanoparticles: Selective Behavior at the Nano‐Bio Interface

Panagiota Papadopoulou,
Rianne van der Pol,
Niek van Hilten
et al.

Abstract: The membrane‐protein interface on lipid‐based nanoparticles influences their in vivo behavior. Better understanding may evolve current drug delivery methods toward effective targeted nanomedicine. Previously, the cell‐selective accumulation of a liposome formulation in vivo is demonstrated, through the recognition of lipid phase‐separation by triglyceride lipases. This exemplified how liposome morphology and composition can determine nanoparticle‐protein interactions. Here, the lipase‐induced compositional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 97 publications
(160 reference statements)
0
0
0
Order By: Relevance
“…Lipid-based nanoparticles (NPs), including liposomes and solid lipid nanoparticles (SLN), are increasingly used for drug delivery due to their high encapsulation efficiency and ease of surface modification [133,134]. Liposomes, mimicking cellular membranes, consist of hydrophilic and hydrophobic phospholipids that spontaneously form bilayers in aqueous solutions, influencing their size, charge, and rigidity [135,136].…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid-based nanoparticles (NPs), including liposomes and solid lipid nanoparticles (SLN), are increasingly used for drug delivery due to their high encapsulation efficiency and ease of surface modification [133,134]. Liposomes, mimicking cellular membranes, consist of hydrophilic and hydrophobic phospholipids that spontaneously form bilayers in aqueous solutions, influencing their size, charge, and rigidity [135,136].…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…Liposomes, mimicking cellular membranes, consist of hydrophilic and hydrophobic phospholipids that spontaneously form bilayers in aqueous solutions, influencing their size, charge, and rigidity [135,136]. These liposomes are particularly effective in delivering low molecular weight drugs and genes [134][135][136] and are biocompatible and minimally immunogenic [137][138][139][140]. Studies have demonstrated liposomes' ability to encapsulate and enhance the delivery of quercetin, a therapeutic agent, across various applications.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%